(untitled) (African Journal of Biomedical Research, 2023)
Pregnancy-induced hypertension is a serious medical issue in pregnant women globally that consequently causes maternal and perinatal morbidity and mortality. Several risk factors are associated with it. Although significantly associated risk factors of pregnancy-induced hypertension have not yet been satisfactorily identified in the Aljouf area, so we aimed to identify the risk factors of pregnancy-induced hypertension. This is a hospital-based retrospective unmatched case-control study that was conducted at Maternity and children hospital Aljouf Saudi Arabia to identify the associated risk factors of pregnancy-induced hypertension over a period of January 2020 to December 2020. Bivariate logistic regression was applied as required in the multivariate logistic regression. In the end, multivariate analysis was done to identify risk factors for pregnancy-induced hypertension. Of a total of 261 pregnant women divided into 87 cases, among them, 57 (65%) pre-eclampsia/ eclampsia and 30 (34%) gestational hypertension. The multivariable analysis applied for required multiple logistic regression, and tracing significantly associated risk factors for pregnancy-induced hypertension such as ANC visited (adj. OR= 10.22, 95%CI: 3.66 – 28.50, p<0.001), maternal excessive weight gain period of pregnancy (>13 kg) (adj. OR=7.33, 95%CI: 3.05 -17.68, p<0.001), history of abortion (adj. OR=3.56, 95%CI: 1.32-9.56, p=0.012), in addition, history of diabetes mellitus (adj OR= 2.59, 95%CI: 1.02 – 6.47, p=0.043) Our study determined that pregnancy-induced hypertension women develop a greater risk of adverse pregnancy outcomes as compared to pregnant women without hypertension. Therefore, identification of these risk factors would be beneficial for the prevention, management, and reduction of complications of both perinatal and maternal morbidity and mortality